The tomato chloroplast stromal proteome compendium elucidated by leveraging a plastid protein-localization prediction Atlas - Bhattacharya, Oindrila; Ortiz, Irma; Hendricks, Nathan; Walling, Linda L. (Frontiers in Plant Science, 2023)
Tomato (Solanum lycopersicum) is a model species for studying fruit development, wounding, herbivory, and pathogen attack. Despite tomato’s world-wide economic importance and the role of chloroplasts as metabolic hubs and integrators of environmental cues, little is known about the stromal proteome of tomato. Using a high-yielding protocol for chloroplast and stromal protein isolation, MudPIT nano-LC-MS/MS analyses, a robust in-house protein database (the Atlas) for predicting the plastid localization of tomato proteins, and rigorous selection criteria for inclusion/exclusion in the stromal proteome, we identified 1,254 proteins of the tomato stromal proteome. We provide one of the most robust stromal proteomes available to date with empirical evidence for 550 and 105 proteins not previously described for tomato plastids and the Arabidopsis stroma, respectively. The relative abundance of tomato stromal proteins was determined using the exponentially modified protein abundance index (emPAI). Comparison of the abundance of tomato and Arabidopsis stromal proteomes provided evidence for the species-specific nature of stromal protein homeostasis. The manual curation of the tomato stromal proteome classified proteins into ten functional categories resulting in an accessible compendium of tomato chloroplast proteins. After curation, only 88 proteins remained as unknown, uncharacterized or as enzymes with unknown functions. The curation of the tomato stromal proteins also indicated that tomato has a number of paralogous proteins, not present in Arabidopsis, which accumulated to different levels in chloroplasts. As some of these proteins function in key metabolic pathways or in perceiving or transmitting signals critical for plant adaptation to biotic and abiotic stress, these data suggest that tomato may modulate the bidirectional communication between chloroplasts and nuclei in a novel manner. The stromal proteome provides a fertile ground for future mechanistic studies in the field of tomato chloroplast-nuclear signaling and are foundational for our goal of elucidating the dynamics of the stromal proteome controlled by the solanaceous-specific, stromal, and wound-inducible leucine aminopeptidase A of tomato.